Hydraulic and oscillation study of the internal flow in a circular tube with vibrational ball turbulators. (June 2022) - Aghlichanche, Alireza; Ataelahi, Ali; Saadat, Milad; Mohammadi, Omid; Shafii, Mohammad Behshad
Abstract: Flow turbulators have crucial importance in heat transfer and energy harvesting applications. Therefore, in this paper, the hydraulic and vibrational behavior of a flow inside a circular tube with vibrational ball turbulators (VBTs) on an axial elastic wire is experimentally studied for the first time. In this novel design, the elastic wire facilitates turbulence by allowing VBTs to move transversally and rotationally, thus agitating the flow substantially. The effects of diameter and longitudinal distance (pitch) ratios of VBTs, the Reynolds number, and the axial tension of the wire, on the flow friction factor ( f ), in addition to the frequency ( F ) and amplitude ( A ) of the balls are studied. To this end, different ball diameters ( D b  = 8, 10, and 12 mm) and ball pitches ( λ  = 40, 60, and 80 mm) in a tube with a constant inner diameter of Dt  = 26 mm are utilized at Reynolds numbers between 10, 000 and 15, 000. Our results reveal that the balls vibrate with higher amplitudes when their diameter is maximum and, counterintuitively, when their pitch is larger. Meanwhile, the friction factor with VBTs is 17 times that of a plain tube. A correlation is also proposed to predict the flow friction factor as a function of the ball distance ratio ( X = λ/Dt ), diameter ratio ( Y = D b /Dt ), and the Reynolds number. The feasibility of this design for energy harvesting is also evaluated in terms of its power output. This novel design benefits from a straightforward implementation, and the results of this study can be readily used to design more efficient heat exchangers, where a precise picture of the device's hydrodynamic and vibrational response is vital.